Korelasi Kebiasaan Membaca dan Kemampuan Literasi Sains - Rosmalah Yanti; Achmad Riady (Cokroaminoto Journal of Primary Education, 2019)
This study aims to determine the correlation between reading habits and the ability of science literacy in students of SMP Negeri 2 Bua Ponrang. The research method used is quantitative descriptive, to determine the correlation used product moment correlation. The results show that the r count value is smaller than r table, so it can be concluded that there is no significant relationship between reading habits and scientific literacy skills.